Fiscal Institutions in Germany - Heiko T. Burret; Lars P. Feld (Swiss Journal of Economics and Statistics, 2013)
In 2009 Germany introduced a new fiscal rule in its Basic Law. It stipulates that the federal budget must be (structurally) close to balance from 2016 onwards and does not allow (structural) budget deficits in the Laender (states') budgets after 2019. While the already existing debt brakes at the Laender level have relatively wide loopholes, six states do not even seriously consider the introduction of new fiscal rules. In fact, only 9 of the 16 Laender as well as the federal level passed binding consolidation plans. Despite historically high revenues in 2011, most states ran deficits and increased public debt. In this paper, we analyze the German debt brakes at the federal and the Laender levels and assess the probability that the German jurisdictions manage to comply with the constitutional requirements of its debt brake.
Keywords: H30; H60; H72; 330; Fiscal Federalism; German Debt Brake; Fiscal Compact